Predictors of Digit Survival following Replantation: Quantitative Review and Meta-Analysis - Shaterian, Ashkaun; Rajaii, Ramin; Kanack, Melissa; Evans, Gregory R. D.; Leis, Amber (Journal of Hand and Microsurgery, 2018)
Introduction Microsurgical replantation following digital amputation has variable success rates. Sociodemographic factors and surgery-related variables have been shown to influence survival rates; however, few studies have evaluated these data systematically across a combined dataset. Therefore, the objective of this study was to analyze the current literature to identify the predictors of replant survival.Materials and Methods A literature review was performed using the PubMed/Medline database focused on complete digit amputation/replantation studies. Studies were evaluated for patient and surgery-related variables and their respective effects on survival. Statistical analysis was conducted to identify predictors of survival and derive pooled estimates from the combined dataset.Results Thirty-two studies representing more than 6,000 digit amputation/replantation cases met inclusion/exclusion criteria. Statistical analysis revealed the number of venous anastomosis (0 vs. 1 vs. 2), the number of arterial anastomosis (0 vs. 1 vs. 2), and the mechanism of injury (sharp cut versus blunt cut versus avulsion versus crush) to influence replant survival (p < 0.05). The authors failed to find a significant association between survival and the following variables: age, sex, zone of injury, digit number, tobacco use, ischemia time, method of preservation, and use of vein graft.Conclusion Patient- and surgery-related variables affect digit survival following replantation. The etiology of injury can help risk-stratify patients and assist in an informed decision making process, whereas surgery-related factors can guide surgeon practice to improve clinical outcomes following replantation.
Keywords: amputation; digit survival; microsurgical replantation